2010
DOI: 10.1093/icesjms/fsq067
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diet and trophic position of a top predator 10 years after a mass mortality of a key prey

Abstract: Chiaradia, A., Forero, M. G., Hobson, K. A., and Cullen, J. M. 2010. Changes in diet and trophic position of a top predator 10 years after a mass mortality of a key prey. – ICES Journal of Marine Science, 67: 1710–1720. After the disappearance of primary prey, seabirds exhibit gradually decreased breeding performance, and eventually the population size drops. Results are presented of an investigation into the diet of little penguins (Eudyptula minor) at Phillip Island, Australia, during a period when their key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 60 publications
9
69
0
Order By: Relevance
“…Parents may thus target different locations to forage on different prey depending on whether food is to be allocated to the chicks or themselves. Stable-isotope analysis, a method used to determine diet segregation, showed that the diet of adults and chicks exhibited different d 13 C and d 15 N signatures in Little Penguins, suggesting that they do not rely on the same resources and that their foraging zones are different (Chiaradia et al 2010). Finally, long trips could also result from longer time spent foraging, but in the same areas as the ones used for short trips, as suggested by RopertCoudert et al 2004.…”
Section: Discussionmentioning
confidence: 95%
“…Parents may thus target different locations to forage on different prey depending on whether food is to be allocated to the chicks or themselves. Stable-isotope analysis, a method used to determine diet segregation, showed that the diet of adults and chicks exhibited different d 13 C and d 15 N signatures in Little Penguins, suggesting that they do not rely on the same resources and that their foraging zones are different (Chiaradia et al 2010). Finally, long trips could also result from longer time spent foraging, but in the same areas as the ones used for short trips, as suggested by RopertCoudert et al 2004.…”
Section: Discussionmentioning
confidence: 95%
“…details in Chiaradia et al, 2010Chiaradia et al, , 2014. Birds were sexed by bill measurements and weighted with spring scale to the nearest 10 g. Stomach contents were sampled by stomach flushing according to Chiaradia et al (2003Chiaradia et al ( , 2010Chiaradia et al ( , 2012.…”
Section: Study Area and Fieldwork Proceduresmentioning
confidence: 99%
“…Whole blood was freeze-dried, then powdered. Subsamples of powdered materials were weighed to the nearest µg and placed into tin capsules for Chiaradia et al, 2010). The remaining samples were analyzed at the Laboratory of Stable Isotopes of the Estación Biológica de Doñana (LIE-EBD, www.ebd.csic.es/lie/index.html) using a continuous flow isotope-ratio mass spectrometry system (Thermo Electron) consisting of a Flash HT Plus elemental analyzer interfaced with a Delta V Advantage mass spectrometer.…”
Section: Stable Isotope Analysesmentioning
confidence: 99%
See 2 more Smart Citations